PEMANFAATAN MEDIA VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SEKOLAH DASAR - Imeldasari Imeldasari; Tri Utami Salentina; Fitri Yani (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The purpose of this study is to describe the benefits of visual aids to strengthen students' enthusiasm for learning. This study applies a qualitative approach through direct observation and interviews involving one of the educators and third-grade III of elementary school students. Based on the results of the study, it is known that visual media plays a role in increasing students' attention during learning sessions, increasing active involvement during indoor learning activities using visual media, greatly supporting students in mastering the material, being more focused and enthusiastic during learning. The use of visual media has shown effectiveness in building an attractive, communicative, and enjoyable learning environment so that it has an effect on increasing students' learning motivation.